Impact of Information Technology on Human Resource Management Procurement Functions: A Case of a Nigerian University - Babaita, Isiaka Sulu; Rafiu, Amosa Jimoh; Aremu, Suleiman Ahmed (Universiti Utara Malaysia Press, 2018)
Information Technologys (IT) role in Human Resource Management (HRM) has attracted minimal interest and attention in the academia industry. The few empirical studies available did not examine the effect of IT on HRM on a comparative basis. Therefore, this study seeks to examine the nexus between IT and HRM procurement process in Nigerian Universities (education sector) with reference to the University of Ilorin. Other objectives are to:(i) examine the extent to which IT influences the HR procurement functions (ii) determine the nature of relationship that exist between/among IT tools and HR procurement functions. Questionnaire was served to the entire 50 members of the staff of the University HR department being census approach. Two hypotheses stated were tested using regression and correlation analysis. The findings revealed that IT has a significant effect on HR procurement functions and that IT tools and HR procurement functions are correlated. The study concludes that IT impacts strongly on HR Procurement activities. This study recommends that the management of Nigerian higher Institutions, inclusive of University of Ilorin, should consistently upgrade their HRIT software to cover a significant number of HR activities in line with the best HR practice as its long-term benefits exceed the pains of its initial cost.